Hydrogen assisted intergranular cracking of alloy 725: The effect of boron and copper alloying. (15th July 2022) - Taji, Iman; Hajilou, Tarlan; Ebner, Anna Sophie; Scheiber, Daniel; Karimi, Shabnam; Plesiutschnig, Ernst; Ecker, Werner; Barnoush, Afrooz; Maier-Kiener, Verena; Johnsen, Roy; Razumovskiy, Vsevolod I.
Abstract: To overcome the Hydrogen embrittlement (HE) susceptibility of the standard Alloy 725 (Mod A), two alloys with minor alloying modifications with B (Mod B) and B+Cu (Mod C) were produced. Then, the intergranular cracking susceptibility was investigated on bi-crystal beams by electrochemical in situ micro-cantilever bending test. The atom probe tomography and first principles calculations were employed to capture and calculate the grain boundary (GB) segregation and its effect on the GB cohesion. Cross-sectional view of the bent beams showed the superior resistance of Mod B against HE by facilitating the GB dislocation transfer/generation. While bending Mod A sample in hydrogen environment leads to form a sharp intergranular cracking, Mod B showed some nano-voids/cracks mostly in dislocation slip bands and rarely in GB path. However, a reduction of strength was observed in load-displacement (L-D) curves of Mod B. The addition of Cu, although not participated in GB segregation, compromised the lost strength of Mod B. In Mod C, after bending in H-charged condition, the nano-voids were formed in GB, but no load drop in L-D curves nor crack propagation in post-deformation observations was detected. The micro-alloying proposed in this study could be an important contribution to the future developing of H resistant alloys via GB segregation engineering. Graphical Abstract: ga1 Highlights: Micro-alloying with Cu and B improves the H resistance of Nickel superalloy. In-situ micro cantilever bending method was used alongside DFT calculations. B tends to accommodate at grain boundaries facilitating dislocation transferability. Cu causes in solid solutions strengthening.